The Relationship between Interest in Learning Physical Education and Basic Abilities in Playing Football - Nanta Lasmana; Kartono Pramdhan; Ricky Ferrari Valentino (Journal of Physical and Outdoor Education, 2026)
The research conducted by the author is a study on the relationship between Interest in Learning Physical Education and Basic Ability to Play Football. This study is a quantitative descriptive study using a correlational method that aims to determine the correlation (relationship) between the two variables. Variable X is Interest in Learning and variable Y is Basic Ability to Play Football. The population in this study were all students who took extracurricular activities. The sample used in this study is part of the population so that the subjects of this study were students in grades 4, 5, 6, Male who took the interest in learning and basic ability test for football 30 students. The sampling technique used Total Sampling. The instrument used in this study forinterest in learning used a Questionnaire and Basic Ability to play football used a Basic Skills Test for playing football, both of which will be modified using a Likert scale. This analysis can be done by statistical testing, namely the correlation test processed with the SPSS Version 29.00 program. The results of the correlation analysis of the relationship between interest in learning physical education and basic ability to play football are known to have a p value of 0.532> 0.05, indicating a significant positive relationship between Interest in Learning Physical Education and Basic Ability to Play Football.